Determinación del costo de producción de quesos en la empresa Gonzanamalac Cia.Ltda., del cantón Gonzanama, provincia de Loja, periodo: agosto–septiembre / 2014 - Encalada Alejandro, Deicy Rocio (2015)
This research work entitled: "DETERMINATION OF COST OF PRODUCTION OF CHEESE IN THE COMPANY GONZANAMALAC CIA. LTDA, GONZANAMÁ CANTON, LOJA PROVINCE, PERIOD. AUGUST-SEPTEMBER / 2014 ", was developed in order to determine the cost of production of cheese in the company GONZANAMALAC CIA. LTDA. which it was necessary for the application of cost accounting, whose productive activity lacks a control system production costs. Also disclosed is the owner of this company the result obtained by determining the total cost of production of cheeses. Note that this work was made according to the Regulation of Academic System of the National University of Loja, Carrera Accounting and Auditing, prior to obtaining degree in Accounting and Auditing, CPA. With the completion of this investigation were met all objectives, starting with the inventories of raw materials and existing winery, property and rights of the company supplies; logging of economic activities in the journal and the use of various supporting documents and cost control. Finally it is concluded that the design and application of accounting records, allowed real results, so it is recommended to continue the process of determining the cost of cheese production in GONZANMALAC CIA. LTDA., And the implementation of cost accounting in order to become an effective tool to provide its own efforts to make the best decisions and guide the operation of the company so that it can develop efficiently